2015
DOI: 10.1016/j.jiac.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of pulmonary cryptococcosis in non-HIV patients in Japan

Abstract: It is crucial to consider the presence of UDs and meningoencephalitis for the choice of antifungals and treatment duration for cryptococcosis in non-HIV patients. Three- and six months-administration of azoles for pulmonary cryptococcosis with or without UDs, respectively is reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 17 publications
4
68
0
2
Order By: Relevance
“…Our findings in immunocompetent individuals have expanded the value of serum CrAg in the diagnosis of diffuse lesion in immunocompetent patients, supporting the results of previous studies that the most common CT findings of pulmonary cryptococcosis was multiple pulmonary nodules/masses of different diameters [18][19][20][21]. Similar to previous reports, our study also found that the most common symptoms of pulmonary cryptococcosis patients included cough and sputum, [5,[22][23][24] with no significant specificity( Table 1). Our laboratory examinations, including leucocyte, neutrophil, lymphocyte, Hb and PLT levels, showed no significant difference between immunocompetent and immunodeficient groups ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings in immunocompetent individuals have expanded the value of serum CrAg in the diagnosis of diffuse lesion in immunocompetent patients, supporting the results of previous studies that the most common CT findings of pulmonary cryptococcosis was multiple pulmonary nodules/masses of different diameters [18][19][20][21]. Similar to previous reports, our study also found that the most common symptoms of pulmonary cryptococcosis patients included cough and sputum, [5,[22][23][24] with no significant specificity( Table 1). Our laboratory examinations, including leucocyte, neutrophil, lymphocyte, Hb and PLT levels, showed no significant difference between immunocompetent and immunodeficient groups ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…As discussed above, cryptococcal infection seems likely to cause localized pulmonary lesions in HIV-infected patients similar with that in HIV-negative patients [1–4], although cavitation of the nodules seems to be more common in HIV-infected patients. The imaging modality of Chest CT scan used in our study is more sensitive to reveal pulmonary lesions [15].…”
Section: Discussionmentioning
confidence: 99%
“…In human immunodeficiency virus (HIV)-negative patients, pulmonary cryptococcosis (PC) has been extensively studied and nodular masses are the most common radiological manifestations [1–4]. However, PC in HIV-infected is less well defined.…”
Section: Introductionmentioning
confidence: 99%
“…to cause endovascular infection and endocarditis is very low. Interestingly, cryptococcosis occurs more frequently in immunocompetent patients than in immunocompromised patients in China [7][8][9][10] . The mechanism of this is not clear.…”
Section: Discussionmentioning
confidence: 99%